Advocacy for Teacher Leadership Opportunity, Preparation, Support, and Pathways - Lovett, Susan (Springer International Publishing, 2018)
This book advocates for an alternative to the hierarchical positioning of leaders. It proposes to value leadership practices which emerge from collective concerns about learning and the realisation that collegial interactions offer opportunities for rich explorations of pedagogy and new understandings to be developed. The book draws upon illustrative examples from a longitudinal study of early career teachers, entitled "Teachers of Promise: Aspirations and realities". It explores matters of personal ambition, support from significant others, and barriers to teacher leadership. It shows that these vary from context to context and individual to individual. Examples highlight the ways in which each teacher's experience has been enabled and constrained by different considerations. In combination, the examples offered demonstrate the need for the teaching profession to be more systematic in identifying and supporting talented teachers who could be the leaders of learning for tomorrow. The book shows that individuals themselves need to have an openness to consider how they might become more effective teachers through their engagement in leadership work. This, it suggests, involves developing a different conception of leadership to counter the prevailing view that leadership is typically positional and defined by its distance from classroom teaching. The more promising portrayal is to link teacher leadership explicitly with learning.